Numerical research on rock breaking by abrasive water jet-pick under confining pressure. (August 2019) - Liu, Songyong; Cui, Yuming; Chen, Yueqiang; Guo, Chuwen
Abstract: Conical pick bears great cutting force, shock, vibration and friction in breaking rock. In order to improve rock breaking efficiency and reduce cutting force as well as pick wear, high-pressure water jet assisted rock breaking technology and abrasive water jet-pick combined rock breaking method have been proposed. Numerical models of abrasive water jet-pick combined rock breaking under confining pressures are established based on FEM combined with SPH which validity are verified by experiment. A 3D numerical model is established to investigate the influence of confining pressure and jet pressure on rock breaking performance of abrasive water jet-pick. Numerical result shows that, when confining pressure increasing from 0MPa to 20MPa, stress concentration area extends on the rock and the cutting force increases by 46.69% during single pick breaking rock. However, the cutting force of abrasive water jet-pick with jet pressure of 30MPa increases by only 21.9% under the same conditions. Confining pressure can inhibit propagation of tensile stress in rock. And most tensile stress area in rock is transformed to compressive stress area, which is harder to break under confining pressure. As a result, cutting force and wear is more serious. Moreover, the cutting force decreases with the increase of abrasive water jet pressure. The reduction rate of cutting force reaches 38.14% when jet pressure increases from 0MPa to 46MPa. At the same time, stress concentration area around the rock crushing crater is more obvious, rock crushing crater and cutting groove is larger, and the weakening effect of abrasive water jet on rock strength is even more significant.